2012
DOI: 10.1586/erv.12.64
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on replication-incompetent nasal influenza virus vaccines

Abstract: Influenza is an emerging as well as resurging contagious disease with a worldwide impact on public health. Although broad administration of the licensed influenza virus (IFV) vaccines has mitigated the disease in many countries over the years, there are intrinsic problems associated with them. The study under evaluation reports that a novel PB2-knockout nonreplicating nasal IFV vaccine has been generated with the capacity to confer protection of mice against live IFV challenges. Moreover, an exogenous gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Due to safety concerns in the young and asthmatics, and limited efficacy in the elderly, LAIV is only recommended for immunocompetent, non-asthmatic patients between the ages of 2–49 (Ambrose et al, 2012; Belshe et al, 2008; Powers et al, 1991). One study has found that combining inactivated and LAIVs is well-tolerated and efficacious in elderly individuals (Tang, 2012; Treanor and Betts, 1998). Therefore, there is great interest and need to improve the immunogenicity of IIV and RIV or the safety of LAIV, and implement new vaccination strategies that prevent infection in susceptible populations.…”
Section: Sciiav Applicationsmentioning
confidence: 99%
“…Due to safety concerns in the young and asthmatics, and limited efficacy in the elderly, LAIV is only recommended for immunocompetent, non-asthmatic patients between the ages of 2–49 (Ambrose et al, 2012; Belshe et al, 2008; Powers et al, 1991). One study has found that combining inactivated and LAIVs is well-tolerated and efficacious in elderly individuals (Tang, 2012; Treanor and Betts, 1998). Therefore, there is great interest and need to improve the immunogenicity of IIV and RIV or the safety of LAIV, and implement new vaccination strategies that prevent infection in susceptible populations.…”
Section: Sciiav Applicationsmentioning
confidence: 99%
“…Two Key Paper Evaluation articles bring the issue up-tothe-minute with critical reviews of recently published primary work from the field [14,15].…”
Section: Suryaprakash Sambharamentioning
confidence: 99%